ANALISIS PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS PERUSAHAAN CONSUMER GOODS INDUSTRY - Rezki Nugraha, Rispantyo & Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2017)
The purpose of this study to analyze the effect of working capital efficiency,liquidity, and solvency on profitability of the company's Consumer Goods Industry inBEI. The study population was 37 Consumer Goods Industry company listed inIndonesia Stock Exchange in 2013-2015. Samples were taken through purposivesampling method as many as 31 companies. The data source is a secondary datacompiled from financial statements of the company's Consumer Goods Industry.Data analysis technique used descriptive statistics, classic assumption test, multiplelinear regression analysis, t-test, F, and the coefficient of determination. The surveyresults revealed that the working capital efficiencyhas positive and not significanteffect on profitability, liquidityhas positive and not significant effect on profitability,solvencyhas negative and significant effect on the profitability.Keywords: working capital efficiency, liquidity, solvency, profitability